2021
DOI: 10.1002/anie.202014426
|View full text |Cite
|
Sign up to set email alerts
|

Tetraimido Sulfuric Acid H2S(NtBu)4—Valence Isoelectronic to H2SO4

Abstract: The valence isoelectronic imido analog H2S(NtBu)4 (1) of sulfuric acid H2SO4 was synthesized, isolated, and characterized by NMR spectroscopy and high‐resolution X‐ray charge density analysis. The latter reveals strongly polarized Sδ+−Nδ− bonds with virtually no double bond character. The easy‐to‐polarize S−N bonds are an advantageous and versatile feature of sulfur nitrogen ligands, which enables them to adapt to different electron requirements of various metal cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The tetraimido sulfate ligand family also represents a platform to investigate d‐metal exchange coupling, which was applied for Co II and Mn II [15] . Sulfur offers great flexibility in the complex geometry while the harder nitrogen atoms ensure an optimal coordination mode around the metal center, resulting in a great synergy [25,27–29] . Lanthanide complexes are easily accessible through metathesis reactions and for that purpose, lithium precursors are convenient to use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetraimido sulfate ligand family also represents a platform to investigate d‐metal exchange coupling, which was applied for Co II and Mn II [15] . Sulfur offers great flexibility in the complex geometry while the harder nitrogen atoms ensure an optimal coordination mode around the metal center, resulting in a great synergy [25,27–29] . Lanthanide complexes are easily accessible through metathesis reactions and for that purpose, lithium precursors are convenient to use.…”
Section: Introductionmentioning
confidence: 99%
“… [15] Sulfur offers great flexibility in the complex geometry while the harder nitrogen atoms ensure an optimal coordination mode around the metal center, resulting in a great synergy. [ 25 , 27 , 28 , 29 ] Lanthanide complexes are easily accessible through metathesis reactions and for that purpose, lithium precursors are convenient to use. However, our recent work showed that the successful optimization of the magnetic properties is limited by LiHal co‐complexation.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the dianionic species [P{N(H)Ph}(NPh respectively. [24] Alongside, few research groups have contributed to the transition metal complexes of these polyimido anions. Collins et al have obtained various mononuclear Ni(II) complexes of the mono-anionic [Ph 2 P(NSiMe 3 ) 2 ] À having PN 2 Ni ring(s), 29 (Figure 5a).…”
Section: Dehnicke Et Al Have Studied Neutral Mono Functionalizedmentioning
confidence: 99%
“…All of these complexes provide two separate chelating N−P−N sites at opposite ligand faces, comprising either one of a) the di(amino) arrangement of the type P(NH) 2 , b) the di(imino) arrangement of the type PN 2 , or c) the mixed amino imino arrangement of the type P(N)(NH). Recently, Stalke and co‐workers have isolated the sulfur analogue of the species 25 and 22 , the tetra(imido)sulphate dianion [S(NR) 4 ] 2− and the neutral amido‐imido sulfuric acid [S(NHR) 2 (NR) 2 ], respectively [24] …”
Section: Introductionmentioning
confidence: 99%
“… [17] We have been already successful employing those ligands to d‐block SMMs with the [MeS(N t Bu)] − ligand in [Co{(N t Bu) 3 SMe} 2 ], (with U eff =75 cm −1 , T B =2.6 K and a hysteresis loop at 2 K), [18] accompanying of a series of complexes with the [S(N t Bu) 4 ] 2− anion. [ 19 , 20 ] This fuelled the idea to transfer the ligand concept to f‐block metals. First results are presented in here.…”
Section: Introductionmentioning
confidence: 99%